Real-world evaluation of nivolumab in patients with non-nasopharyngeal recurrent or metastatic head and neck cancer: A retrospective multi-center study by the Turkish Oncology Group (TOG). - Akyildiz, Arif; Guven, Deniz Can; Koksal, Baris; Karaoglan, Beliz Bahar; Salim, Derya Kivrak; Sutcuoglu, Osman; Aksoy, Sercan (Lippincott Williams & Wilkins, 2024)
[Abstract Not Available]
Special Clinical Science Symposia -- MAY 29-29, 2024 -- ELECTR NETWORK